Haematopoietic depletion in vaccine-induced neonatal pancytopenia depends on both the titre and specificity of alloantibody and levels of MHC I expression. Issue 30 (9th July 2015) - Bell, Charlotte R.; MacHugh, Niall D.; Connelley, Timothy K.; Degnan, Kathryn; Morrison, W. Ivan
Highlights MHC I-specific alloantibodies play a dominant role in Bovine Neonatal Pancytopenia. 50% of Pregsure-vaccinated cows produce MDBK-MHC I-specific alloantibodies. Pregsure-vaccinated cows produce variable titres and specificities of alloantibody. Alloantibody damage to haematopoietic cells is due to their high MHC I expression.